Legal Pluralism as a Theoretical Programme - Emma Patrignani (Oñati Socio-Legal Series, 2014)
This paper reconstructs the development of the status of the theory of legal pluralism: while originally the term has been used as descriptive label referring to a situation observed in the world, nowadays a more sophisticated understanding of the role of the concept is needed. The epistemology of social sciences can help us make sense of the multifarious literature on legal pluralism, and of the different conceptions of the term that have been proposed. More specifically, legal pluralism is here devised as a theoretical programme and its influence on the production of social-scientific knowledge is analysed. The investigation concentrates on the role of the concept in the selection of relevant data and on the intelligibility structure imposed on them.